East‐Central Asian Climate Evolved With the Northward Migration of the High Proto‐Tibetan Plateau. Issue 14 (30th July 2019) - Zhu, Chenguang; Meng, Jun; Hu, Yongyun; Wang, Chengshan; Zhang, Jian
Abstract: The evolution of Cenozoic climate patterns in Asia has been linked to uplift of the Tibetan Plateau (TP), retreat of the Paratethys Sea, and global cooling. However, less attention has been placed on the latitudinal change of the TP. Here we report new climate modeling to explore how modern climate changes as a function of topographic growth and spatial migration of the TP. Our results show that the northward displacement of the uplifted proto‐TP within the subtropics can significantly affect the wind and precipitation pattern over East‐Central Asia. By compiling proxy‐based climatic records, paleolatitudinal and paleoelevational evolution models of the proto‐TP, and in comparison with previous modeling under a global paleogeography, we suggest that the northward migration of the proto‐TP in the Paleogene could have intensified the aridity in Central Asia, but its influence on East Asian precipitation and monsoonal circulation could be dependent on the paleogeography and other boundary conditions. Plain Language Summary: The evolution of the Asian monsoons and aridification of Asia's interior are thought to be driven by Tibetan‐Himalayan uplift. Recent geological observations suggest that the uplifted proto‐Tibetan Plateau (proto‐TP) migrated northward in the subtropics since the early Eocene and reached its present position by the latest Oligocene. We therefore simulated the effects of this process on East‐Central Asian climate. Our climate modeling shows the northward migration of the high proto‐TP from 21–29°N to 29–37°N can significantly change the present‐day wind and precipitation patterns over East‐Central Asia. Especially, Central Asia become drier because of the displacement of the anomalous dry belt caused by large‐scale atmospheric subsidence. We further suggest that forcing by the paleolatitudinal migration of the high proto‐TP within the subtropics from the Eocene to the earliest Miocene could have driven the Central Asian paleoclimate to drier conditions, but migration might not be the sole parameter that governed the East Asian monsoon during the Paleogene. Key Points: The high proto‐Tibetan Plateau migrating northward can notably influence the modern East‐Central Asian climate system Central Asian aridification increased with the northward migration of the proto‐Tibetan Plateau in the Paleogene The impact of Paleogene proto‐Tibetan Plateau migration on East Asian climate could be dependent on boundary conditions